A REVIEW ON MOUNT SEMERU ERUPTION WARNING ARTICLE: A CRITICAL DISCOURSE ANALYSIS - David Geba Abi Anandi (Journal of English Language and Culture, 2022)
Mount Semeru had erupted three times in 2021. The last eruption caused many victims. The fact that there were many death toll and citizens affected by the eruption, many people started to blame the PVMBG, as the responsible government agency to the disaster since their duties are to monitor the volcano activities and to give prior warning to the citizens who lived near the volcano. A news article was written a few days after the mount erupted. This article contains many explanations and clarifications from the PVMBG. Therefore, this current study aims to review a news article entitled “Mount Semeru eruption warning issued on Dec 1, PVMBG claims”. There are two problems addressed in this study; 1) “What social wrong does Tempo’s text reveal in the Mount Semeru eruption warning article?”; and 2) “What ideology does Tempo’s text reflect in the Mount Semeru eruption warning article?”. In answering these problems, the writer employed critical discourse analysis. The method used in this study is Critical Discourse Analysis. Furthermore, Fairclough's four stages and three dimensions approach of CDA were used. The sentences which show the social wrong are chosen and analyzed by using the transitivity. The findings show that the social wrong is the PVMBG insists that they are not responsible for the numbers of victims caused by the eruption. The PVMBG needs the social wrong since they try to keep their good image and professionalism. The solutions to the problem are related to the involvement of the citizens in the group message and the improvement of the geological mitigation programs.